2007
DOI: 10.1177/1352458506074177
|View full text |Cite
|
Sign up to set email alerts
|

The relation of focal white matter signal abnormality and focal volume loss in multiple sclerosis

Abstract: There were two aims to this study. First, to explore how the reduction in the volume of abnormal T2-signal intensity associated with white matter (WM) lesions in multiple sclerosis (MS) relates to tissue loss resulting from focal pathology inside lesions. Second, to demonstrate that this volume of abnormal T2-signal intensity underestimates the actual size of the region to which the direct effects of lesion activity extend. For these purposes, we used deformation field analysis to quantify the evolution of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…26 However, as in adult-onset studies, the correlation between MRI-visible lesions and brain volumes is only moderate. We propose that the relationship between visible inflammatory (T2w) lesions and focal tissue damage (T1w lesions) and volumetric measures relates to a process whereby axonal transection in white matter lesions contributes to retrograde neuroaxonal degeneration and loss of anterograde transsynaptic pathways.…”
Section: Discussionmentioning
confidence: 95%
“…26 However, as in adult-onset studies, the correlation between MRI-visible lesions and brain volumes is only moderate. We propose that the relationship between visible inflammatory (T2w) lesions and focal tissue damage (T1w lesions) and volumetric measures relates to a process whereby axonal transection in white matter lesions contributes to retrograde neuroaxonal degeneration and loss of anterograde transsynaptic pathways.…”
Section: Discussionmentioning
confidence: 95%
“…A close relationship has been demonstrated between cognitive impairment and third ventricular width or volume, possibly reflecting the clinical effect of thalamic atrophy 11 12 25–28. Furthermore, Kezele et al demonstrated a close association between focal tissue loss in periventricular lesions and local ventricular enlargement 29. Considering the central portion of the brain as the most frequent location of MS lesions, especially in the early disease stage, disruption of functionally important white matter tracts may explain the relation between ventricular enlargement and subsequent clinical disability.…”
Section: Discussionmentioning
confidence: 99%
“…Atrophy is greater in the vicinity of lesions [35 ], focal inflammatory activity in the white matter predicts atrophy, albeit weakly [37], and postmortem histopathology of segmentally demyelinated axons shows axonal swellings associated with local ATP depletion [33 ]. Taken together, these data suggest that both mechanisms are contributing to the neurodegenerative process.…”
Section: Insights Into the Mechanisms Of Neurodegeneration Based On Imentioning
confidence: 79%
“…Kezele and colleagues tested this hypothesis by measuring the regional atrophy around short cerebral association and projection fibres, and comparing this to the atrophy around the very long corticospinal tract [35 ]. The greatest atrophy was, in fact, observed around the short cerebral projection and association tracts, whereas the long corticospinal tract showed the least atrophy.…”
Section: Insights Into the Mechanisms Of Neurodegeneration Based On Imentioning
confidence: 99%